2017
DOI: 10.1002/admt.201700134
|View full text |Cite
|
Sign up to set email alerts
|

3D Inkjet Printing of Electronics Using UV Conversion

Abstract: additional research challenges, namely in their depo sition, conversion, and interfaces. The opportunity for AM more generally has been determined by its functionality over more traditional manufacturing methods; where geometrical complexity is an inherent strength. The realization of mul tifunctional AM (MFAM) could augment this opportunity through the processing of multiple materials to gain further com ponent function in the final part. [7][8][9][10][11][12] Pre vious work in multiple material deposition ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 72 publications
0
47
0
Order By: Relevance
“…3D printing has demonstrated great potential for studying flow and transport processes in porous media due to the unprecedented freedom of design offered by this technique [12][13][14][15]. The concept of using 3D printing to replicate complex porosity in rocks has been reported by Head et al and Ishutov et al [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…3D printing has demonstrated great potential for studying flow and transport processes in porous media due to the unprecedented freedom of design offered by this technique [12][13][14][15]. The concept of using 3D printing to replicate complex porosity in rocks has been reported by Head et al and Ishutov et al [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Saleh et al who demonstrated 3D printing of integrated electronic devices by combining UV sintering of a conductive ink based on silver nanoparticle (AgNP), with UV curing of an insulator to house the features is one potential solution to this problem. 95 Despite rapid development of materials in research organisations, warranty issues make it unattractive to print with custom materials due to the high cost of the printer and propriety nature of the hardware and print process. The availability of multi-head FDM printers as well as options in splicing filaments for multimaterial printing using a single nozzle printer make this technique currently best equipped for the fabrication of integrated chemical devices.…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%
“…Material jetting employing photopolymerization is similar to stereolithography, where acrylate-type photopolymers are deposited and exposed to ultraviolet light [ 1 ]. Promising material systems for future applications involve resins modified with carbon-based fillers, ceramics, and metals [ 2 , 3 , 4 , 5 , 6 ]. Factors that mutually influence the material jetting process are machine and material parameters, including liquid material viscosity, shear-thinning effects and surface tension, print head nozzle design, print speed, and droplet velocity and frequency [ 7 ].…”
Section: Introductionmentioning
confidence: 99%